Traditional Houses and Architecture of Kashkadarya - Xushnazavovich, Qurbanov Ravshan; Хammаtоvnа Shamahmudova Мuhayo; Mirkamol o‘g‘li, Sodiqov Mirasrol (European Journal of Life Safety and Stability (2660-9630), 2021)
This article provides information about the traditional houses of the folk national architecture of Kashkadarya and what rooms are available due to the climatic conditions of Kashkadarya. At the same time, it is said about the local construction materials used. In the article, special attention was paid to the waiting rooms of guests in rich apartments. And, in particular, information about local customs and cultural norms, namely about the bridge over the Kashkadarya.